The tough slog of a moderate religious state: Highly educated Muslims and the problem of intolerance in Indonesia - Suntana, Ija (HTS teologiese studies, 2022)
This study aims to analyse the perspectives of Muslim students on pluralism and freedom of religion, as well as the worship place establishments, holy book assessments and practices of other religions. This study uses a cohort-based quantitative method through data collection, interviews and documentation, which involves 1300 respondents from 13 state Islamic higher education institutions in Indonesia. In order to collect information from the respondents, this research uses an online questionnaire. It also conducts online interviews to directly confirm the information obtained from the questionnaire. This research discovers that Muslim students are tolerant in accepting plurality and religious diversity, yet intolerant in the holy book assessment, place of worship establishments and practices of other religions.Contribution: This study contributes towards developing a persuasive concept concerning religious moderation, commenced by analysing socio-theological perspectives of highly educated society.